Penerapan Case Based Reasoning Untuk Penentuan Obat Berbasis Algoritma Nearest Neighbor - Sopiyan Dalis; Mochomad Wahyudi (Universitas Bina Sarana Informatika, 2016)
Self-medication is a community effort to self-medicate. But in practice, self-medication can be a source of error treatment (medication error) due to limited public knowledge of the drug and its use. Case-Based Reasoning (CBR) is a problem solving technique based on knowledge gained by past experience. Application of CBR is not new but has been widely applied in solving solution or process data by using the previous case. Meanwhile, the nearest neighbor algorithm is an approach to search for cases by calculating the closeness between the new cases with the old case, which is based on matching the weights of a number of existing features. This study aims to apply CBR for the determination of drugs by people for himself (self-medication), through the selection of cases indications or symptoms, specific conditions and experience allergies, drug name, nutritious substances, usability, use, side effects and drug interactions. So expect the process to be more appropriate self-medication. Keywords: Case Based Reasoning, Nearest Neighbor algorithm, Self-medication